Effects of stress concentration on fibre reinforced composites - Dong, Jonathan (2016)
A study on the stress concentration of composite plates with a central circular hole subject to axial and bending loads is presented in this paper. The stress concentration of composite plates with a central circular hole subject to axial and bending loading was studied with the aid of finite element analysis. It is shown that geometry has a significant effect on stress concentration, while fibre volume fraction has little effect. The stress concentration factor decreases with increasing hole diameter to plate width ratio. Further analysis shows stress concentration is strongly dependent on anisotropy and the stress concentration factor increases with the longitudinaltransverse moduli ratio.